Reinforcement model considering slip effect. (1st November 2019) - Wang, Zhuo-Han; Li, Lei; Zhang, Yi-Xin; Zheng, Shan-Suo
Highlights: A simple and efficient reinforcement model considering slip effect is developed. The rebar strain is revised in tensile stage to consider the reinforcement slip. The elastic modulus of the steel bar is reduced in model. The model is implemented into a fiber beam-column element model using OpenSEES. The effects of key parameters on the column slip displacement are investigated. Abstract: Reinforcement slip in the beam-column joint or column footing may significantly influence the lateral displacement of a reinforced concrete (RC) column. A simple and efficient reinforcement model to consider the reinforcement slip effect is presented in this study. The proposed model utilizes a bilinear stress-strain relationship which assumes the increase in rebar strain contributed by reinforcement slip in tensile stage. The slip is calculated by the assumption of stepped bond stress distribution along development length. Then the proposed model is simplified by an extensive parametric investigation. After that, the proposed model is implemented into a fiber beam-column element model. The results from the modified fiber model are compared with the test results of RC columns and compared with the results from the conventional fiber model and zero-length fiber model. The modified fiber model agrees well with the experimental results in the column stiffness, followed by the zero-length fiber model. However, the conventional fiber model may significantly overestimate the column stiffness. Moreover, the modified fiber model shows a good accuracy in simulating the total lateral displacement of the column and shows success in capturing the lateral displacement contributed by reinforcement slip deformation. The results confirm the reliability of the proposed model for both section and member level. Finally, a comprehensive parametric study is accomplished to evaluate the effects of concrete, rebar, section, and axial load properties on the lateral displacement response of an RC column contributed by reinforcement slip deformation.